2016
DOI: 10.1186/s12872-016-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor agonists and heart failure in type 2 diabetes: systematic review and meta-analysis of randomized and observational studies

Abstract: BackgroundThe effect of glucagon-like peptide-1(GLP-1) receptor agonists on heart failure remains uncertain. We therefore conducted a systematic review to assess the possible impact of GLP-1 agonists on heart failure or hospitalization for heart failure in patients with type 2 diabetes.MethodsWe searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL) and ClinicalTrials.gov to identify randomized controlled trials (RCTs) and observational studies that addressed the effect of GLP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…We identified four meta-analyses of GLP-1 receptor agonists for assessment (Table 2) [12, 41, 55, 56]. One meta-analysis of trial-level data reported comparisons between GLP-1 receptor agonists and non-GLP-1 receptor agonists [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified four meta-analyses of GLP-1 receptor agonists for assessment (Table 2) [12, 41, 55, 56]. One meta-analysis of trial-level data reported comparisons between GLP-1 receptor agonists and non-GLP-1 receptor agonists [12].…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 shows that the GLP-1 receptor agonist drug class and its members were not associated with increasing risk of MACE components, including heart failure, on the basis of results of three meta-analyses [12, 41, 56], although there was evidence associating exenatide with increased risk of arrhythmia (OR 2.83; 95% CI 1.06–7.57) [41]. …”
Section: Resultsmentioning
confidence: 99%
“…Thus, it may be concluded that the effect of liraglutide on LVEF is, if anything, modest and probably not clinically relevant. ; this finding was, however, based on a limited number of events (five in total) and a very wide CI [33]. Nevertheless, these data were confirmed in the second meta-analysis reporting the HR for exenatide, albiglutide and liraglutide (Table 2) [34].…”
Section: Effects Of Liraglutide On Cardiac Function and Cardiovasculamentioning
confidence: 79%
“…The effects of GLP-1RAs on the risk of developing HF in patients with T2D have been analyzed by two large metaanalyses of phase-II/III randomized controlled trials (RCTs; Table 2) [33,34]. The first meta-analysis provided data for all the GLP-1RAs combined and for each individual GLP-1RA (albiglutide, dulaglutide, exenatide and liraglutide) [33].…”
Section: Glp-1ras and Heart Failure Riskmentioning
confidence: 99%
See 1 more Smart Citation